ISOLATION, CHARACTERIZATION AND IDENTIFICATION OF EFFICIENT POTASH SOLUBILIZING BACTERIA AND FUNGI - R. REKHA; K. R. SREERAMULU (The Bioscan, 2015)
Potassium is the major cat ion among the trinity of nutrients required in large quantities by most of the crops. The availability of soluble form of potassium in soils is low and more than 90% of it exists as insoluble and in combined form with silicates. An attempt was made in this study to isolate efficient potash solubilizing microorganisms from rhizosphere soils of banana plantations enriched with different concentrations of potassium salts with muscovite. The most efficient potash solubilizing bacteria identified were Bacillus mucilaginosus (UASKB 102) and Pseudomonas fluorescence (UASKB 101). Similarly the two fungal isolates which were identified as efficient Potash solubilizers were Aspergillus niger (UASKF 102) and Aspergillus terreus (UASKF 101) and any one of this can be routinely used by farmers as a potash solubilizing biofertilizer in crop cultivation.